Transurethral resection of bladder tumor-based bladder preservation therapy for refractory high risk non-muscle invasive bladder cancer: Current landscape and future directions - Sun, Xinghui; Dai, Tianzeng; Xu, Lihui (Frontiers in Surgery, 2023)
Bladder cancer is the most common malignant tumor of urinary system worldwide. Approximately 75% of patients with bladder cancer present with non-muscle-invasive bladder cancer (NMIBC), which is effectively managed with transurethral resection of bladder tumor(TURBT). For refractory high risk NMIBC, patients are typically treated by radical cystectomy(RC). TURBT deserves further evaluation. Growing evidence suggests that repeated TURBT-based bladder-sparing approaches may improve oncological outcomes and quality of life in highly selected patients. Novel imaging techniques and biomarkers may aid in patients selection and postoperative surveillance. With growing interest in adding immunotherapy to refractory bladder cancer, TURBT based approaches enable the bladder preservation therapy for high risk NMIBC. Here we summarize the current landscape, biomarkers for surveillance, and future directions for applying TURBT-based bladder preservation therapy.